Heavy metal concentrations in the blood and the risk of allergic diseases for South Korean children and adolescents - Choi, Hye-Seon; Ahn, Hye-Young; Woo, Jin-Ju (International Journal of Engineering and Technology, 2019)
The purpose of this study was to investigate the effects of heavy metal concentration in the blood on allergic diseases in Korean children and adolescents using the Korean National Health and Nutrition Examination Survey (KNHANES) data. For the study, a secondary analysis of the data collected via the sixth KNHNES in the first year (2013) was conducted. The study subjects were 1,065 children. All the data were analyzed through a two-sided test at a significance level Î±=.05 using SPSS 24. As a result, the geometric mean concentrations of lead, mercury and cadmium in the blood were 1.25Â±0.03 ãŽ/dL, 1.95Â±0.08 ãŽ/L and 0.35Â±0.03 ãŽ/L. As for allergic diseases, 6.2% of the children were diagnosed by doctors with asthma, 17.7% with atopic dermatitis, and 24.7% with allergic rhinitis. When mercury concentration in the blood increased by 0.1 ãŽ/L, the possibility of allergic rhinitis prevalence was significantly increased by 1.31 times (p=.040). The above results indicate that heavy metal concentration in the blood of children affects allergic diseases. Therefore, in the future, an analytic epidemiological study should be conducted to investigate allergic diseases and related factors considering the characteristics of each heavy metal.Â